HUBUNGAN KEMAMPUAN BERPIKIR KRITIS DAN SELF-DIRECTED LEARNING DENGAN LITERASI DIGITAL PADA GURU MI - Firnandi, Khanza Nabila; Noviekayati, IGAA; Pratitis, Niken Titi (UJoST- Universal Journal of Science and Technology, 2024)
The era of digitalization requires teachers to be proficient in using and utilizing digital media and mastering digital competencies in it. The purpose of this study is to prove the relationship between digital literacy, critical thinking skills, and self-directed learning in MI teachers. This study uses quantitative research methods with data collection in the form of a psychological scale. The research subjects totaled 154 teachers who were divided into 12 educational institutions in Pakong District, using a purposive sampling technique, namely teachers with an age range of 27-60 years who had Android mobile phones and could access WhatsApp. The research data analysis method uses Spearman Rho's non-parametric analysis assisted by SPSS version 25 for windows. The results of the study show that critical thinking skills have a positive correlation with digital literacy with an rho value of 0.381. Self-directed learning is also proven to have a positive correlation with digital literacy with an rho value of 0.442 and a significance level (p <0.01). The results of the research in this thesis also identify that self-directed learning has a more dominant effective contribution to digital literacy than critical thinking skills, which is 19.5%.